ALKYLATING AGENT ETHYL METHANE SULPHONATE (EMS) INDUCED VARIABILITY IN TWO ECONOMICALLY IMPORTANT MUTANTS OF VICIA FABA L. - RUBINA PERVEEN; ALKA; SAMIULLAH KHAN (International Journal of Pharma and Bio Sciences, 2012)
Seeds of Vicia faba L. varieties 05/249 local and 05/233 HBP were subjected to induce variability in faba bean an economically important crop 0.02%, 0.04%, 0.06%, and 0.08% of ethyl methane sulphonate (EMS). The mutagenic treatments of ethyl methane sulphonate caused biological damage, which was measured by M1 parameters. Data on various quantitative traits such as, plant height, days to flowering, and days to maturity, pods length, number of fertile branches/plant, number of pods / plant, number of seeds / pod, 100 seeds weight (g) and total plant yield (g) were recorded in both the varieties of faba bean. The variants were morphologically quite distinct, as compared to the control and to each other. The increase in mean value of plant height, fertile branches/ plant and pods/plant were found to be significant in both the varieties, though seeds/ pod differed from the control but the values were insignificant . Number of seeds/pod and 100 seeds weight did not show any significant difference. The total plant yield did not show significant in var. 05/233 HBP but it is found significant in var. 05/249 local.